Differentiated Instruction for Special Needs in Inclusive Schools: A Preliminary Study. (5th February 2016) - Rachmawati, Mira Aliza; Nu'man, Thobagus Muh.; Widiasmara, Nur; Wibisono, Susilo
Abstract: This study aims to develop the instruments used in implementation of differentiated instruction among students in inclusive schools. The method used in this study was integrating between theoretical consideration based on the literatures and empirical evidences from the interview with the teachers of inclusive schools in Yogyakarta. The result of the study showed the need of assessment in several dimensions, both teachers and students. In the teacher's context, the evaluation on the relevant competencies need to ensure the successful process of teaching and learning on special needs students in inclusive schools. The competencies evaluated among teachers contains three dimensions: (1) Readiness to operate the differentiated instruction (2) Understanding on large difference of student's interest; and (3) Decision on the learning method based on student's learning profile. The assessment needed among students was developed by observation form that will be used by teachers to evaluate their students. This form contained the evaluation of student's readiness to receive differentiated instruction in learning process, the evaluations of student's interests, and the evaluation of student's learning style based on Gardner's multiple intelligences theory.